2008
DOI: 10.1080/00016340701671929
|View full text |Cite
|
Sign up to set email alerts
|

Endometriomas are more frequent on the left side

Abstract: Our results confirm a left lateral predisposition of endometrioma. This predisposition may be caused by the presence of the sigmoid colon in the left side of the pelvis, which decreases peritoneal fluid movement. Our findings may support the transplantation theory of the origin for endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
(20 reference statements)
7
27
0
2
Order By: Relevance
“…On the other hand, our results showing the left lateral predisposition of ovarian endometriotic cyst are in agreement with previous reports [8][9][10]. However, these studies did not investigate whether endometrioma side is related with endometriosis severity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, our results showing the left lateral predisposition of ovarian endometriotic cyst are in agreement with previous reports [8][9][10]. However, these studies did not investigate whether endometrioma side is related with endometriosis severity.…”
Section: Discussionsupporting
confidence: 93%
“…However, these studies did not investigate whether endometrioma side is related with endometriosis severity. Left lateral predisposition of endometriosis and endometriomas could be explained by anatomical and hormonal factors [8][9][10]. According to Vercellini et al, the presence of sigmoid colon on the left side may delay elimination of the regurgitated endometrial cells coming through the fallopian tubes during menstruation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We did, however, find an increased occurrence of ovarian endometrioma on the left side, compared with the right side, confirming the findings of others (18)(19)(20). Based on Sampson's theory of retrograde menstruation (3), it has recently been postulated that the deposition of viable endometrial cells, shed through the fimbrial ends of the uterine tubes, occurs equally on both sides.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast a study carried out in Scandinavia showed that left ovarian involvement (62.8%) was more frequent than right (Sznurkowski et al, 2008) In Asians Physiological cysts were 47 (28.1%). Simple follicular cysts were 17(10.2%) and corpus luteal cysts 30(18%).…”
Section: Discussionmentioning
confidence: 73%